Konstruksi Sosial Pasien Terhadap Pengobatan Alternatif Jari Sakti Kecamatan Wirolegi Kabupaten Jember - Nadilla Ragil Saputri (FAKULTAS ILMU SOSIAL DAN ILMU POLITIK, 2026)
Public trust in traditional alternative medicine is quite high. The reality in society is that efforts to resolve health problems are not limited to medical treatment, but also through alternative therapies. This study examines patients’ views on alternative medicine as a means of healing. The reseach problem is how patients construct their social views oh the Jari Sakti alternative medicine in Wirolegi District, Jember Regency. This study employed a qualitative reseacrh method with a phenomenological approach. Informants were selected using purposive sampling, with data collected through observation, interviews and documentation. Data analysis involved three stages: data reduction, data presentation, And a conclusion drawing. This study utilized Peter L Berger and Thomas Luckmann’s social construction theory to examine the reseach problem formulation. Social construction theory states that a social construct is formed through three interrealated processes: externalization, objectification, and internalization. The results indicate that during the externalization stage, informants obtain information from others and attempt to delve deeper into the Jari Sakti alternative medicine. Furthermore, during the objectification stage, individulas accept the information and follow up by trying the Jari Sakti alternative treatment. In the final stage, namely the internalization stage, the community accepts and believes in the existence of alternative medicine an alternative way of seeking treatment besides medical treatment.
Finalisasi Repository/HASYIM Agustus 2026
Keywords: alternative medicine; other healing efforts; social constructions